A Kinematic Kinetic Energy Backscatter Parametrization: From Implementation to Global Ocean Simulations. (26th November 2020) - Juricke, S.; Danilov, S.; Koldunov, N.; Oliver, M.; Sein, D. V.; Sidorenko, D.; Wang, Q.
Abstract: Ocean models at eddy‐permitting resolution are generally overdissipative, damping the intensity of the mesoscale eddy field. To reduce overdissipation, we propose a simplified, kinematic energy backscatter parametrization built into the viscosity operator in conjunction with a new flow‐dependent coefficient of viscosity based on nearest neighbor velocity differences. The new scheme mitigates excessive dissipation of energy and improves global ocean simulations at eddy‐permitting resolution. We find that kinematic backscatter substantially raises simulated eddy kinetic energy, similar to an alternative, previously proposed dynamic backscatter parametrization. While dynamic backscatter is scale‐aware and energetically more consistent, its implementation is more complex. Furthermore, it turns out to be computationally more expensive, as it applies, among other things, an additional prognostic subgrid energy equation. The kinematic backscatter proposed here, by contrast, comes at no additional computational cost, following the principle of simplicity. Our primary focus is the discretization on triangular unstructured meshes with cell placement of velocities (an analog of B‐grids), as employed by the Finite‐volumE Sea ice‐Ocean Model (FESOM2). The kinematic backscatter scheme with the new viscosity coefficient is implemented in FESOM2 and tested in the simplified geometry of a zonally reentrant channel as well as in a global ocean simulation on a 1/4° mesh. This first version of the new kinematic backscatter needs to be tuned to the specific resolution regime of the simulation. However, the tuning relies on a single parameter, emphasizing the overall practicality of the approach. Plain Language Summary: At the currently affordable resolution, ocean models as part of climate models are facing the challenge of adequately representing mesoscale eddies, the weather systems of the oceans. The models tend to lose too much kinetic energy, which strongly reduces the strength of eddies in the simulations and causes large, systematic model errors. The so‐called backscatter approach feeds energy back into the ocean to compensate for some of the lost energy. This leads to substantially better simulations of eddy variability as well as the oceanic mean currents and a reduction of systematic model errors in the distribution of salt and heat, as shown by comparison with observations. The key advantage of the scheme proposed here is that it can be implemented at no additional computational cost. Key Points: A new simplified kinematic backscatter parametrization with a new viscosity coefficient is introduced The new scheme is tested in a channel setup and substantially increases eddy kinetic energy In global eddy‐permitting simulations the new scheme leads to bias reductions in SSH variability and temperature